Антропологічний вимір сфер буття людини: генезис поглядів - Завальнюк, Володимир Васильович; Завальнюк, Владимир Васильевич; Zaval'njuk, Vladimir (My University, 2009)
The article is devoted a n t h r o p o l o g y as g e n e r a l a p p r o a c h in philosophy. The m a i n feature of h u m a n life, which distinguishes him from existence of other living organisms, consists in that it flows simultaneously in n a t u r e , society and culture. In society with his economic, political, legal, ideological and other spheres it c o n d u c t s life as a social creature. And, finally, in a c u l t u r e , it lives in t h e world of spiritual values of religious, moral, artistic, philosophy. K n o w l e d g e of m a i n t e n a n c e of c o n s t i t u e n t s of c o n c e p t a p p a r a t of h u m a n o l o g y with the use of legal experience allows to put in order the existent variety of t e r m s , perfect a concept apparat, define correlation of termino-concepts in this sphere, to perfect the language of jurisprudence, and also to define a role and place of m a n in anthropological researches.
Завальнюк В. В. Антропологічний вимір сфер буття людини: генезис поглядів / В. В. Завальнюк // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 63-71.
Keywords: філософська антропологія; антропологія права; методологія юридичної науки; людина в праві; философская антропология; антропология права; методология юридической науки; человек в праве; philosophical anthropology; legal anthropology; metodologіya yuridichnoї science; h u m a n in law